PEDAGOGICAL PRINCIPLES OF ORGANIZING INDIVIDUAL ACTIVITY OF STUDENTS IN BIOLOGY LESSONS (Academicia Globe: Inderscience Research, 2022)
This article is about effective educational and methodological tools used in organizing and conducting biology lessons.